Fakta Negatif Budaya Banjar Dalam Pembentukan Perilaku Bullying Siswa SMA - Muhammad Andri Setiawan; Ali Rachman (JURKAM: Jurnal Konseling Andi Matappa, 2018)
The establishment of bullying behavior of high school students is basically not only influenced by social interaction factor but also influenced by the environment. This study aims to conduct a thorough review of the negative facts of Banjar culture in the establishment of bullying behavior of high school students by taking a study on the students of SMA Negeri 12 Banjarmasin. The research method used is to conduct a literature review on the formation of bullying behavior. The result of research shows that the negative facts of Banjar culture have an impact on the behavior of 'bullying'. In an empathetic perspective, it occurs because of the overwhelming feeling, in an assertive perspective because of the habit of silencing the problem and lastly in the perspective of confirmation because of the attitude that tends to simplify life and ignore the feelings of others.